Transforming molecular diagnostics learning: the power of gamification in higher medical education - Zhu, Hua; Zeng, Wei; Chen, Li (Frontiers in Education, 2025)
IntroductionTraditional teaching models in molecular diagnostics often fail to engage students effectively, leading to superficial learning and limited development of core competencies.MethodsThis study evaluated the integration of gamified learning with collaborative inquiry learning to enhance student motivation and competencies improvement among 47 biotechnology undergraduates at Guilin Medical University. Participants engaged in a four-unit “Gene Detective” game, solving clinical cases through molecular techniques, earning skill points, and collaborative inquiry learning in group discussions.ResultsData from skill assessments, self-reported competency scales, final exam scores from the concurrent course, and post-course questionnaires revealed significant improvements in core competencies especially in critical thinking, curiosity, creativity and communication skill, with a positive correlation between game-based skill values and academic performance. Over 88% of students reported high engagement, and 79.6% reported increased learning interest.DiscussionWhile the hybrid model successfully promoted motivation and competencies development, challenges in enhancing collaborative skill and providing individualized support were identified. The findings underscore the potential of gamification in medical education and highlight future directions, including AI-driven personalization and refined collaborative tasks, to optimize learning outcomes.